2012
DOI: 10.1161/atvbaha.112.254730
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Yes-Associated Protein Expression After Arterial Injury Is Crucial for Smooth Muscle Phenotypic Modulation and Neointima Formation

Abstract: Objective Abnormal proliferation and migration of vascular smooth muscle cells (SMCs) are the key events in the progression of neointima formation in response to vascular injury. The goal of this study is to investigate the functional role of a potent oncogene YAP in smooth muscle phenotypic modulation in vitro and in vivo. Methods and Results In vitro in cell culture and in vivo in both mouse and rat arterial injury models YAP expression is significantly induced and correlated with the vascular SMC syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
141
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(152 citation statements)
references
References 32 publications
(46 reference statements)
11
141
0
Order By: Relevance
“…Besides TxA2, isoprostanes may also act through the TP receptor on the surface of smooth muscle cells and initiate the migration from media to intima via YAP/TAZ activation. Previous studies have reported that YAP is activated in VSMCs of the neointima (39). We propose that thromboxane acts through TP to induce YAP/TAZ activation to promote normal physiological wound healing in response to vascular injury.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Besides TxA2, isoprostanes may also act through the TP receptor on the surface of smooth muscle cells and initiate the migration from media to intima via YAP/TAZ activation. Previous studies have reported that YAP is activated in VSMCs of the neointima (39). We propose that thromboxane acts through TP to induce YAP/TAZ activation to promote normal physiological wound healing in response to vascular injury.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, emerging evidence shows that YAP is induced after arterial injury and that its activation promotes smooth muscle phenotypic switching and neointima formation (39,40). This led us to investigate the function of YAP/TAZ in TxA2-and TP receptor-induced cellular signaling and VSMC migration and proliferation.…”
Section: Tp-specific Agonists [1s-[1␣2␣(z)3␤(1e3s*)4 ␣]]-7-[3-[3-mentioning
confidence: 99%
“…In the vascular system, smooth muscle-specific deletions of YAP result in profound cardiac defects and vascular abnormalities (28). The inductions of YAP expression and activation following arterial injury enhance neointima formation and the subsequent stenosis as a result of the unrestrained smooth muscle cell proliferation (15). We demonstrate that perturbations of YAP/TAZ in ECs resulted in significant changes in EC growth, indicating that YAP/TAZ are essential for proliferation and cell cycle progression of ECs.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies have reported that YAP/TAZ serve as major mechanotransducers responding to extracellular biophysical cues, such as cell geometry and matrix stiffness, in modulating stem cell fate (14). YAP has been shown to mediate vascular remodeling in the progression of carotid stenosis (15). Two of the YAP/TAZ transcriptional targets, cysteine-rich angiogenic inducer 61 (CYR61) and connective tissue growth factor (CTGF), are highly expressed in atherosclerotic or injured, but not in normal, human arteries (16,17).…”
mentioning
confidence: 99%
“…For example, Yap expression is significantly increased in smooth muscle cells following carotid artery injury, where it promotes smooth muscle proliferation and migration (Wang et al, 2012). Although Yap and Taz are thought to mediate largely redundant functions in many tissues, deletion of Yap in developing smooth muscle is sufficient to disrupt smooth muscle formation, producing thin arterial walls and enlarged vessel lumens in the left carotid and thoracic arteries (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%